AN EMERGING CHRISTIAN PERSPECTIVE ON ECOLOGY: AS SHAPED BY SCRIPTURE, COSMOLOGY AND CONTEMPORARY SCIENCE. - O’Mahony, Donal (Journal of Dharma, 2001)
Readers can be grateful to Dr. Augustine Thottakara for inviting a wide range of writers from very diverse religious backgrounds to share their thoughts on the eco-dynamics of their respective religions with special focus on the future. The global community today is asking scientists, economists, politicians, and other experts to address the challenge of our deteriorating environment. Solutions to this complex and multifaceted crisis do not come easy. But the Christian Churches above all should have a prophetic word to offer. For no religion would dare to say that the ecological concerns for our planet and our belief in the God of all life should not go hand in hand.